Characterization of maize roothairless6 which encodes a D-type cellulose synthase and controls the switch from bulge formation to tip growth - Li, L.; Hey, S.; Liu, Sanzhen Z.; Liu, Q.; McNinch, C.; Hu, H. C.; Wen, T. J.; Marcon, C.; Paschold, A.; Bruce, W.; Schnable, P. S.; Hochholdinger, F. (My University, 2016)
Root hairs are tubular extensions of the epidermis. Root hairs of the monogenic recessive maize mutant roothairless 6 (rth6) are arrested after bulge formation during the transition to tip growth and display a rough cell surface. BSR-Seq in combination with Seq-walking and subsequent analyses of four independently generated mutant alleles established that rth6 encodes CSLD5 a plasma membrane localized 129 kD D-type cellulose synthase with eight transmembrane domains. Cellulose synthases are required for the biosynthesis of cellulose, the most abundant biopolymer of plant cell walls. Phylogenetic analyses revealed that RTH6 is part of a monocot specific clade of D-type cellulose synthases. D-type cellulose synthases are highly conserved in the plant kingdom with five gene family members in maize and homologs even among early land plants such as the moss Physcomitrella patens or the clubmoss Selaginella moellendorffii. Expression profiling demonstrated that rth6 transcripts are highly enriched in root hairs as compared to all other root tissues. Moreover, in addition to the strong knock down of rth6 expression in young primary roots of the mutant rth6, the gene is also significantly down-regulated in rth3 and rth5 mutants, while it is up-regulated in rth2 mutants, suggesting that these genes interact in cell wall biosynthesis.
Citation: Li, L., Hey, S., Liu, S. Z., Liu, Q., McNinch, C., Hu, H. C., . . . Hochholdinger, F. (2016). Characterization of maize roothairless6 which encodes a D-type cellulose synthase and controls the switch from bulge formation to tip growth. Scientific Reports, 6, 12. doi:10.1038/srep34395
Keywords: Lateral Root Initiation; Cell-Walls; Phosphorus Acquisition; Arabidopsis-Thaliana; Anchored Protein; Hair Development